Peran dan Fungsi Badan Pengawas Pemilihan Umum dalam Penegakan Hukum Pemilu Tahun 2019 Menuju 2024 - Tahe, Saifuddin; Yasin, H. M.; Jaya, Alwi (Al-Ishlah: Jurnal Ilmiah Hukum, 2021)
This study aims to determine and analyze the Election Supervisory Agency of Sinjai Regency's role and function in the Law Enforcement of the 2019 Election and the strategies carried out by the Election Supervisory Agency of Sinjai Regency to optimize its role in the Law Enforcement of the 2019 Election. As for this research's benefits, it is hoped that it will improve the organizing institution, especially the Election Supervisory Agency of Sinjai Regency, to lead to the 2024 General Election. This research is empirical legal research. The types of data used in this study include primary data and secondary data. Preliminary data and secondary data that have been collected during the survey are then arranged systematically and analyzed qualitatively according to their validity and reliability. Based on the description of the results and discussion, the Election Supervisory Agency of Sinjai Regency role and function in enforcing Law No. 7 of 2017 in the 2019 Election are considered good enough. However, problems must be fixed and improved in the 2024 General Elections and getting attention from the Election Supervisory Agency of Sinjai Regency as there are still money politics, some non-neutral State Civil Servants and Village Heads, the use of State facilities, places of worship and educational places as means of campaigns and activities that disturb public order.